FIGURE 2 in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 2. Some intertidal habitats on Trindade Island. A, C, F, Parcel das Tartarugas: A, C, May 2012. F, June 2016. B, D, ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 8, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...